Factors that Affect User Satisfaction of Dukcapil Application (Dukcapil Dalam Genggaman) in Surakarta Regency - Darmawan, Andreas Bayu; Nugroho, Rino Ardhian (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2020)
Electronic Government (e-Government) has been implemented in Indonesia at both the central and regional levels, where Information and Communication Technology (ICT) is integrated with public services in order to increase effectiveness, efficiency, and transparency. Surakarta has succeeded in creating an application that operates online which can be used to access population administration services, namely Dukcapil application (Dukcapil dalam genggaman in Indonesian term). This application is designed to make it easier for some people of Surakarta who are still experiencing problems if they have to directly access population administration services, whether constrained in terms of time, energy, and cost. As part of population administration services and population information systems, user satisfaction is important for Dukcapil Dalam Genggaman because it is related to the quality of the services provided and the success of implementing the application. User satisfaction can be influenced by several factors. Therefore, this study will examine the factors that influence user satisfaction of Dukcapil Dalam Genggaman. These factors were adapted from a model for measuring the level of user satisfaction with information systems, namely End User Computing Satisfaction (EUCS), which measures satisfaction based on content, accuracy, format, ease of use, and timeliness. This study aims to determine the effect of these factors on user satisfaction of Dukcapil Dalam Genggaman. The questionnaire was distributed to users of Dukcapil Dalam Genggaman and successfully obtained a sample of 107 users. The data analysis used is multiple linear regression. It was found that content, accuracy, ease of use, and timeliness have a significant effect on user satisfaction of Dukcapil Dalam Genggaman. Meanwhile, the format does not have a effect on user satisfaction of Dukcapil Dalam Genggaman. Based on these findings, the Department of Population and Civil Registration of Surakarta is recommended to develop Dukcapil Dalam Genggaman by focusing on the factors that affect user satisfaction of the application.